Continued insights into virus clearance validation across continuous capture chromatography. Issue 9 (21st January 2021) - Angelo, James M.; Potter, Kevin; Müller‐Späth, Thomas; Xu, Xuankuo; Li, Zheng Jian; Ghose, Sanchayita
Abstract: Multi‐column capture chromatography (MCC) has gained increased attention lately due to the significant economic and process‐related advantages it offers compared to traditional batch mode chromatography. However, for wide adoption of this technology in the clinical and commercial space, it requires scalable models for viral validation. In this study, additional viral validation studies were conducted under cGLP guidelines to assess retro‐(X‐MuLV) and parvo‐virus (minute virus of mice) clearance across twin‐column continuous capture chromatography (CaptureSMB) to supplement work previously performed. A surrogate model was validated using standard batch mode chromatography equipment based on flow path modifications to mimic the loading strategy employed in CaptureSMB. In addition, aged resin was used in this surrogate format to assess the impact of resin lifetime on viral clearance during continuous capture operation. The impact of column loading was also explored to shed light on the viral clearance mechanisms of protein A chromatography in overloading conditions. The proposed approach greatly simplifies MCC virus validation studies, and provides a robust strategy for regulatory filing of continuous biomanufacturing processes. Abstract : In this study, the authors present a surrogate model system for performing viral validation for two‐column continuous protein A capture chromatography, which is readily achieved on conventional FPLC systems. The authors show that neither loading nor resin age have a significant impact on the ability to clear virus in a multi‐column protein A format over conventional batch chromatography.